2014
DOI: 10.1540/jsmr.50.78
|View full text |Cite
|
Sign up to set email alerts
|

Effect of colonic distension on gastric adaptive relaxation in rats: barostatic evaluation using an orally introduced gastric balloon

Abstract: While the gastrocolonic reflex has been known, the cologastric relationship has not been clarified especially with regard to gastric adaptive relaxation. Therefore, in this study we have examined the correlation between gastric adaptive relaxation and colonic distension. Male Sprague-Dawley rats were used after fasting for 18 h. Colonic distension was performed by injecting 2.2 ml of air into a colonic balloon inserted into the colon for 5 min in conscious state. After urethane anesthesia, gastric adaptive rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…The gastro‐colic reflex is well understood, but how modulation of lower gastrointestinal function impacts on the upper gastrointestinal symptoms is not well understood. The colo‐gastric reflex, demonstrated in animal studies, shows that colonic distension inhibits gastric adaptive relaxation and this may be the basis of a change in the colonic microbiota's effect on dyspeptic symptoms . In humans, limited indirect evidence exists for the influence of lower gastrointestinal function on upper gastrointestinal symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gastro‐colic reflex is well understood, but how modulation of lower gastrointestinal function impacts on the upper gastrointestinal symptoms is not well understood. The colo‐gastric reflex, demonstrated in animal studies, shows that colonic distension inhibits gastric adaptive relaxation and this may be the basis of a change in the colonic microbiota's effect on dyspeptic symptoms . In humans, limited indirect evidence exists for the influence of lower gastrointestinal function on upper gastrointestinal symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The colo-gastric reflex, demonstrated in animal studies, shows that colonic distension inhibits gastric adaptive relaxation and this may be the basis of a change in the colonic microbiota's effect on dyspeptic symptoms. 21 In humans, limited indirect evidence exists for the influence of lower gastrointestinal function on upper gastrointestinal symptoms. In the study by Ong and colleagues, IBS patients randomised to high versus low FODMAP diets found that a high FOD-MAP diet induced upper gastrointestinal symptoms including nausea and heartburn.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation is the inhibition of cologastric reflex due to reduced colonic distension (because of decreased colonic hydrogen production) with LFD. Cologastric reflex was initially demonstrated in animal studies, in which colonic distension inhibited gastric adaptive relaxation 27 . In humans, indirect evidence of the presence of cologastric reflex comes from few studies—a study including IBS patients that reported increased upper GI symptoms with high FODMAP diet 28 ; a pediatric study demonstrating reduction of dyspeptic symptoms with relief of constipation by laxatives 29 ; and a recent study reporting relief of dyspeptic symptoms in FD patients after Rifaximin induced change in colonic microbiota 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Subjects with confirmed slow transit constipation often have stool frequency within the normal range [63], but may present with concurrent dyspeptic, reflux or LPR symptoms. Rectal or colonic barostat balloon distension has also been shown to trigger colonic pain and increased motility [5], reduce oesophageal, gastric and small intestinal motility [6,7] and impair gastric accommodation [8,9]. Patients more sensitive to rectal balloon distension have been found to have higher indigestion, reflux, abdominal pain, constipation and IBS scores, which highlights the multiple different colonic reflexes that may be triggered by distension generating both upper and lower GI symptoms [64].…”
Section: Optimising Management Of Refractory Gord and Lprmentioning
confidence: 99%
“…The association between irritable bowel syndrome (IBS) and both refractory GORD and LPR suggests a common pathogenesis. IBS subjects are known to have increased sensitivity to colonic distension causing pain and increased contractility [5], but colonic distension has also been found to affect upper gut motility [6][7][8][9] and increase reflux events in physiological studies [10]. Treating GORD and LPR symptoms refractory to proton pump inhibitor (PPI) therapy remains challenging, but the effect of downstream colonic distension or occult constipation on treating GORD and LPR to date has been largely ignored.…”
Section: Introductionmentioning
confidence: 99%